2021
DOI: 10.1155/2021/6698649
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Propagation Characteristics of Hydraulic Fracture in Clayey-Silt Sediments

Abstract: The low permeability of clayey-silt hydrate reservoirs in the South China Sea affects the thermal and pressure conductivity of the reservoir, which is difficult to spread to the far end of the wellbore and achieve commercial gas production. In this respect, enhancing the permeability to assist depressurization is necessary. Hydraulic fracturing is a promising reservoir stimulation method for gas hydrate reservoirs. Up to now, majorities of research focus on the fracability of hydrate-bearing sandy sediments, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…(c) Confining pressure: 15 MPa; height: 15 cm. Figure reproduced with permission from ref . Copyright 2021, Hindawi.…”
Section: Hydraulic Fracturingmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) Confining pressure: 15 MPa; height: 15 cm. Figure reproduced with permission from ref . Copyright 2021, Hindawi.…”
Section: Hydraulic Fracturingmentioning
confidence: 99%
“…Another key aspect of fracturing experiments is determining the distribution and shape of fractures, including macroscopic fractures, and performing computed tomography (CT) scanning. For clay−silt marine NGHRs, Lu et al 58 explored the effect of hydraulic fracturing under different confinement pressures and used CT scanning to observe the formation and development of fractures, as shown in Figure 7. They found that the effect of hydraulic fracturing increased as the confining pressure increased and the clay−silty sediment under a high confining pressure exhibited high plasticity and was prone to plastic expansion.…”
Section: Experimental Study Of Hydraulic Fracturing In Nghrsmentioning
confidence: 99%
“…Similarly, the decomposition zone of clayey silt exhibits significant artificial fracturing capacity. Higher confining pressure and plastic deformation will result in the formation of horizontal fractures and small fracture zones, leading to the creation of numerous microfractures around the wellbore (Lu et al, 2021a). Optimizing the parameters such as artificial fracture permeability, half-length and width can significantly reduce the fluid flow resistance at the bottom of the wellbore decomposition zone, promoting pressure diffusion and hydrate decomposition (Xu et al, 2023).…”
Section: Optimization and Control Of Reservoir Transport Capacitymentioning
confidence: 99%
“…One of the key factors causing unsatisfactory trial production capacity is poor reservoir permeability. , Reasonable artificial reconstruction is a promising route to improve reservoir seepage conditions. , Many active explorations have been carried out, including hydraulic fracturing, near-well reconstruction, chemical stimulation, etc., by laboratory experiments and large-scale numerical simulations. In terms of experiments, hydraulic fracturing tests were carried out with NGH-free sediments, , sandy NGH-bearing sediments, and clay silt NGH-bearing sediments. The fracturing mode of unconsolidated NGH-free sediments is related to fluid intrusion and shear action at the crack front as well as the internal interface, which is different from the tensile fracture mode in intact rocks . For the NGH-bearing sediments, the tensile fracture similar to rocks is observed; meanwhile, there are some additional behaviors of fluid erosion perforation and widening cracks .…”
Section: Introductionmentioning
confidence: 99%